Dynamic self-configuration of user QoS oriented to cognitive network - FENG Guang-sheng; WANG Hui-qiang; MA Chun-guang; LI Bing-yang; ZHAO Qian (Tongxin xuebao)
To solve the rapid drop of user QoS under network congestion, improve the accuracy of user QoS and advance the ability of dynamic adjustment, a dynamic self-configuration method for user QoS protection was proposed. Utility function was introduced to initialize the priorities of user QoS, and then the active features of cognitive network and the interruption management were utilized to determine the priorities and also correct them dynamically by cognitive nodes. Simulation results show that the proposed method is better than traditional DiffServ, and able to guarantee user QoS effectively in case of network congestion.